2012
DOI: 10.1007/s10531-012-0279-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of impact of climate change on Rhododendrons in Sikkim Himalayas using Maxent modelling: limitations and challenges

Abstract: Integration of climate change aspects in biodiversity management is one the fundamental requirements for long term biodiversity conservation. The explicit modelling of the biodiversity in response to climate change is the primary requirement for making any adaptation strategy. With Himalayan ecosystem in mind and Rhododendron as the species of concern, the current paper models the biogeography of the genera Rhododendron which are found intermixed in their spatial distribution in Sikkim Himalayas, mainly tree v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 16 publications
1
89
0
6
Order By: Relevance
“…In the Himalaya, neither modelling approaches to predict the response of individual treeline systems nor modelling studies to project future geographic distribution of treeline tree species have been conducted so far. Recently, initial modelling studies with regard to environmental niches of the genus Rhododendron in Sikkim and Betula utilis in Uttarakhand have been published (Kumar, 2012;Singh et al, 2013).…”
Section: Treeline Shiftsmentioning
confidence: 99%
“…In the Himalaya, neither modelling approaches to predict the response of individual treeline systems nor modelling studies to project future geographic distribution of treeline tree species have been conducted so far. Recently, initial modelling studies with regard to environmental niches of the genus Rhododendron in Sikkim and Betula utilis in Uttarakhand have been published (Kumar, 2012;Singh et al, 2013).…”
Section: Treeline Shiftsmentioning
confidence: 99%
“…The WorldClim data are collected from weather stations across the globe, which include altitude, temperature, and rainfall (period 1950-2000) [22]. In the present study, four bioclimatic variables (MAT, TS, MAP and PS) were considered to assess the current climatic conditions.…”
Section: Climatic Datamentioning
confidence: 99%
“…The model suggested that the distribution of both the species would tend to move in the direction of shorter cold seasons. Kumar (2012) has analysed the distribution of Rhododendron species in climate change scenario and pointed out that climate data reliability holds the key to such studies in hilly mountainous terrains.…”
Section: Overviewmentioning
confidence: 99%